1993
DOI: 10.2176/nmc.33.675
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Histamine Receptors in Human Cerebral Arteries

Abstract: Histamine and 2,2-pyridylethylamine, an H1-receptor agonist, (both 10(-8)-10(-3) M) caused contraction of human cerebral artery preparations in the absence of active tension, while dimaprit, an H2-receptor agonist, caused vasorelaxation. The histamine-induced vasoconstriction was blocked non-competitively by tripelennamine, an H1-receptor antagonist. In the presence of cimetidine, an H2-receptor antagonist, histamine-induced contraction was enhanced. The histamine-induced contraction was not affected by phento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Because the selective H 3 receptor agonist imetit failed to initiate any relaxation, our data suggest that the H 3 receptor is not expressed functionally in these types of vessels. These results are in line with previous findings in human cerebral arteries 23 …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Because the selective H 3 receptor agonist imetit failed to initiate any relaxation, our data suggest that the H 3 receptor is not expressed functionally in these types of vessels. These results are in line with previous findings in human cerebral arteries 23 …”
Section: Discussionsupporting
confidence: 94%
“…These results are in line with previous findings in human cerebral arteries. 23 For our future plans to work on this model using human uterine arteries, it was essential to determine whether these vessels can be stored in the incubator for up to 5 days to allow molecular modulation using, for example, antisense/sense vectors introduced into the arterial wall. Our data that endothelium-dependent relaxation to histamine and acetylcholine, as well as the contractile response to phenylephrine, was not modulated during the storage in the incubator suggest that, under these conditions, blood vessel reactivity remained constant over 5 days.…”
Section: Discussionmentioning
confidence: 99%
“…Gokina and Bevan (8, 9) reported that Ca 2+ influx through VDCC might be responsible for over the 80% of histamine-induced sustained contraction (26). The same result was also reported in human cerebral arteries (33) and observed in this study (Fig. 3C, 4, 5B).…”
Section: Discussionsupporting
confidence: 92%
“…In many of the previous studies, in contrast to the present, the locations of the different receptors were not determined. The presence of both H 1 ‐ and H 2 ‐receptors in the cranial arteries seems well established, and the only conflicting result is that of a relaxant H 2 receptor coupled to the endothelium in cerebral arteries (Takagi et al , 1993). However, this study concerned large cerebral arteries and most of the vasculature demonstrated arteriosclerotic changes, which is in contrast to the small calibre arteries used in the present study which were macroscopically free from any arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%